Meniscectomy: Efficiency of physiotherapy protocols (Research, Society and Development, 2025)
The study aimed to understand the effectiveness of physical therapy protocols applied in the rehabilitation process after meniscus tear, considering their contribution to functional recovery and quality of life. Specifically, it sought to contextualize the meniscus tear procedure, addressing its anatomical, physiological, and clinical aspects; describe the effectiveness of the different physical therapy protocols used postoperatively; and identify the main benefits observed in the rehabilitation of patients undergoing surgery, based on the evidence available in the scientific literature. The rationale for the research is to understand the functional and clinical impacts of therapeutic strategies used in the management of meniscal tears, since conservative interventions, when properly implemented, can produce results similar to surgery, reducing costs and risks. Methodologically, the study was conducted through an integrative literature review with a qualitative approach, using specific descriptors in the LILACS, MEDLINE, and PubMed databases, covering publications from the last five years. Full-text articles in Portuguese, English, and Spanish addressing menisectomy and physical therapy protocols applied to knee rehabilitation were included. After screening and full reading, 11 articles comprised the final sample. The results showed that both arthroscopic partial meniscectomy and structured physical therapy promote functional improvement, pain reduction, and improved quality of life. Protocols based on clinical criteria proved more effective, reinforcing the importance of individualized and supervised rehabilitation for functional recovery and the prevention of postoperative complications.